If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9j = 4j + -6 Reorder the terms: 7 + -9j = -6 + 4j Solving 7 + -9j = -6 + 4j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-4j' to each side of the equation. 7 + -9j + -4j = -6 + 4j + -4j Combine like terms: -9j + -4j = -13j 7 + -13j = -6 + 4j + -4j Combine like terms: 4j + -4j = 0 7 + -13j = -6 + 0 7 + -13j = -6 Add '-7' to each side of the equation. 7 + -7 + -13j = -6 + -7 Combine like terms: 7 + -7 = 0 0 + -13j = -6 + -7 -13j = -6 + -7 Combine like terms: -6 + -7 = -13 -13j = -13 Divide each side by '-13'. j = 1 Simplifying j = 1
| 7x=21-(49x-63) | | x^2-4x+y^2+z^2-6z-3=0 | | T^2+16t-36=0 | | 5-8u=-7u | | 8t-9=10t+9 | | 5x=31+2x+11 | | 6x+10-3x=8+2x-5 | | -r^2+8r=0 | | 2cosx-5=0 | | 3y+9=2y-4 | | 6+10-3x=8+2x-5 | | Y=5z-8 | | 15x+3(4x-6)=3x+9-9x | | (2x-4)+X=28 | | 7x=5+3x+19 | | 8h=10h+6 | | x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 | | 2x-4+x=28 | | 24=-8u+5(u+6) | | 2x^2+2y^2-2xy-2x+4y+5=0 | | 3x^2+27x-6.5=0 | | 8(x-3)+9=5x+3(-4+x) | | 15-27=2(21) | | 5w=6w+7 |